The Development of Post-Modern Islamic Boarding Schools (Case Study at IHAQI Creative Pesantren in Bandung) - Nurti Budiyanti; Nurwadjah Ahmad; Andewi Suhartini; Muhamad Parhan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
Religious education is fundamental to be improved, as moral degradation continues to take root around the world. One of the efforts to maintain the value of religious teachings is through the education system, among others through boarding school education. The presence of boarding schools in the middle of society is not only as an educational institution, but also as a religious and religious broadcasting institution. This research uses a qualitative approach with case study methods at IHAQI Boarding School Bandung Creative Boarding School. The results of the study illustrate that historically pesantren continues to change, in the 21st century pesantren developed using the word pondok to